The effects of irrigation methods on some of soil and plant microbial indices using treated municipal wastewater - Negar Nourmahnad; Jahangir Shams; Azita Shams (International Journal of Recycling of Organic Waste in Agriculture)
Shortage of irrigation water is a crucial problem in arid and semi-arid regions. Therefore, application of wastewater in such area seems to be an indispensable solution. The health aspect of the application should be considered by microbial evaluation of soil and plant irrigated with treated wastewater. In this study several irrigation methods were used. Results showed that the filtration reduced the microbial pollution of treated municipal wastewater. The maximum soil pollution was in the surface drip and furrow irrigation with treated municipal wastewater. The least level of total and fecal coliform were in sub-surface drip irrigation at the depth of 30 cm in condition of municipal wastewater reuse. The results of plants revealed that the highest coliforms were seen at the surface drip and furrow irrigation with treated municipal wastewater. The minimum coliforms numbers were observed in the sub-surface drip irrigation method. Therefore, the sub-surface drip irrigation can reduce the wastewater reuse problems at soil and plant. It is the best option to avoid the contamination in landscape.